Thermal Behavior and Hydrogen Production of Methanol Autothermal Reforming Performed Using Oxygen Enrichment and Cu/ZnO/Al2O3/Cr2O3/CeO2 Catalyst - Ho-Shing Wu; Donny Lesmana (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2015)
A fixed-bed reactor designed for the autothermal reforming (ATR) of methanol under adiabatic conditions was constructed to experimentally determine the profile of temperature and catalyst activity generated using the Cu/ZnO/Al2O3/Cr2O3/CeO2 catalyst. The effect of oxygen enrichment in this experiment was investigated, and the experimental results showed that an increase in oxygen concentration correlated with an increase in the temperature of the catalytic bed; by contrast, this increase in oxygen concentration resulted in a reduction of the startup time of the catalyst. Moreover, the reaction temperature was determined to vary with the position within the catalytic fixed bed. © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)